Comparative Study of Cleansing Action of Some Detergents Available in Nepalese Market - Pathak, Arvind; Khadka, Pratima; Karki , Prabin (Nepal Journal of Science and Technology, 2021)
Detergents commercially available in the Nepalese market were studied and several parameters such as surface tension, pH, critical micelle concentration, foaming stability test, hard water test, emulsions stability test were performed. Different medium such as ground water (G.W.), tap water (T.W.), distilled water (D.W.) and 5% ethanol in distilled water were selected for this study. The decrease in surface tension and critical micelle concentration (CMC) in ground water, tap water, distilled water and 5% ethanol in distilled water, ease of cleansing action of the detergents in this medium have been found of the following order: 5% ethanol in distilled water > distilled water (D.W.) > tap water (T.W.) > ground water (G.W.). Among the four detergents, the D1 have shown the least surface tension, CMC value, foam collapsing time, the weight of scum formed when treated with hard water. And maximum emulsion stability of the detergent D1 determines good quality detergent.